Optical Imaging of Pancreatic Innervation - Makhmutova, Madina; Caicedo, Alejandro (Frontiers in Endocrinology, 2021)
At the time of Ivan Pavlov, pancreatic innervation was studied by looking at pancreas secretions in response to electrical stimulation of nerves. Nowadays we have ways to visualize neuronal activity in real time thanks to advances in fluorescent reporters and imaging techniques. We also have very precise optogenetic and pharmacogenetic approaches that allow neuronal manipulations in a very specific manner. These technological advances have been extensively employed for studying the central nervous system and are just beginning to be incorporated for studying visceral innervation. Pancreatic innervation is complex, and the role it plays in physiology and pathophysiology of the organ is still not fully understood. In this review we highlight anatomical aspects of pancreatic innervation, techniques for pancreatic neuronal labeling, and approaches for imaging pancreatic innervation in vitro and in vivo.